MiR-122 direct detection in human serum by time-gated fluorescence imaging. Issue 99 (27th November 2019) - Garcia-Fernandez, Emilio; Gonzalez-Garcia, M. Carmen; Pernagallo, Salvatore; Ruedas-Rama, Maria J.; Fara, Mario A.; López-Delgado, Francisco J.; Dear, James W.; Ilyine, Hugh; Ress, Cristina; Díaz-Mochón, Juan J.; Orte, Angel
Abstract : A new time-gated fluorescence-based imaging method to analyse microRNAs directly from human serum using dynamic chemistry labelling. Abstract : A simple method for direct detection of microRNAs (miRs) in human serum without the use of polymerase amplification is presented, achieving low miR-122 concentrations and importantly, discerning effectively single-base sequence mutations. The method is based on the capture of target miRs with synthetic peptide nucleic acid oligomers, dynamic chemical labelling, separation with quaternary amine microplatforms and detection using time-gated fluorescence imaging.